Peran Orang Tua sebagai Pendidik Iman dengan Pembentukan Moral dan Pembentukan Iman di Gereja Kristen Jawa se-Klasis Banyumas Selatan - Boiliu, Noh Ibrahim; Wiryadinata, Halim; Hidayat, Udin Firman; Purba, Sudiarjo (Sekolah Tinggi Teologi Berita Hidup, 2024)
The central role of parents in the lives of children cannot be replaced or delegated to other individuals or parties. Parents in the GKJ Jeruklegi Margi Rahayu congregation have not fully fulfilled this role. This study aims to determine the role of parents as spiritual educators in shaping the morals and faith of children in the Javanese Christian Church throughout the South Banyumas Classis and to understand the influence of parents' role as spiritual educators on the formation of morals and faith of children in the Javanese Christian Church throughout the South Banyumas Classis. The research method used in this study is qualitative. Based on analysis using Nvivo 12 Software, it is concluded that the role of parents in spiritually educating and accompanying children significantly influences children's relationship with God; The support and advice given by parents to children play a crucial role in shaping the spiritual formation of children and helping family members find a better way of life; Parental guidance and advice demonstrate the family's function in maintaining a harmonious relationship between parents and children; Guidance and advice as important approaches in educating and shaping the faith and morals of children are based on harmonious relationships; In teaching and parenting, parents must understand the importance of using technology wisely in educating children, especially in facing online challenges, and cooperation between husband and wife in instilling religious values in children through everyday experiences.